Analysis of Flavaniod Content From Extract Ethanol Bilajang Bulu Leaf (Merremia vitifolia) - Hasanah, Ella; Ayu, Ni Komang; Puspita, Dela; Sukarti, Sukarti (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2019)
The aim of this research of flavonoid compounds extract from ethanol Bilajang Bulu (Merremia vitifolia). Empirically, Merremia vitifolia was used by people in Luwu, Southern Sulawesi as a cure for diabetes mellitus injury. The research was supported by previous study, which claimed that Merremia vitifolia had an active compound that worked as anti-virus, insecticides, and anti-bacteres. Methods of this research were through preparation of a Merremia vitifolia leafs sample, maseration, extraction, and flavonoid total assesment by using spectrophotometry UV-Vis. The result obtained that the level of flavonoids was 163,4 mg/L or equivalent to 0,01634%.